PENGARUH PERLAKUAN PENDAHULUAN DAN VARIASI METODE DESTILASI TERHADAP KARAKTERISTIK MUTU MINYAK ATSIRI DAUN KAYU MANIS (C. Burmanii) - Nugraheni, Krisnawati Setyaningrum; Khasanah, Lia Umi; Utami, Rohula; Anandhito, Baskara Katri (Jurnal Teknologi Hasil Pertanian, 2016)
This study aims to determine the effect of pretreatment (drying, drying and sun drying) and distillation method (distillation of water and vapor distillation) to the quality characteristics of cinnamon leaf oil. Characteristics of quality of essential oil of cinnamon leaves, essential oil of selected cinnamon leaves from vapor distillation with dry treatment of wind has the highest yield of 0.10161%. Specific gravity, viscosity,refractive index, and solubility in 70% ethanol range from 0.91 - 0.96 g / ml, 0.0023 N.s / m2, 1.48-1.51 and 1: 0.8 - 1: 1.5, respectively. Water vapor distillation with dry wind treatment has a solubility value in the smallest 70% alcohol. The active compounds contained in the volatile oil of leaf from the distillation of water vapor with dry treatment of wind are L-Linalool 34,40%, 1,8-Cineole 18,18%, α-Pinene 13,96% and β-Pinene 9.30%.